Does job security hamper employment prospects? - Carl Magnus Bjuggren; Per Skedinger (Research Institute of Industrial Economics (IFN), 2018)
We investigate the effect of employment protection legislation (EPL) on the propensity to hire workers from unemployment and active labor market programs (ALMPs), utilizing a reform that decreased dismissal costs for small firms only. Using administrative data from Sweden, we find that less stringent EPL increased the share of workers hired from unemployment and some ALMPs. Our results suggest that there was less screening of new hires after the reform, and that liberalization of EPL mitigates the stigma associated with unemployment and participation in ALMPs.
Keywords: J60; J64; K31; H80; 330; Employment protection; Active labor market programs; Unemployment